Personal protective equipment use by health‐care workers in intensive care units during the COVID‐19 pandemic in Japan: comparative analysis with the PPE‐SAFE survey. Issue 1 (4th November 2020) - Unoki, Takeshi; Tamoto, Mitsuhiro; Ouchi, Akira; Sakuramoto, Hideaki; Nakayama, Asami; Katayama, Yukiko; Miyazaki, Satoko; Yamada, Toru; Fujitani, Shigeki; Nishida, Osamu; Tabah, Alexis
Abstract : Aim: We investigated personal protective equipment (PPE) use and supply shortage, training, and adverse events among health‐care workers (HCWs) in the intensive care unit (ICU) during the coronavirus disease (COVID‐19) pandemic in Japan and compared the results with an international survey that used the same methodology. Methods: This Web‐based survey was carried out from 14 April to 6 May, 2020, in Japan and included HCWs directly involved in ICU management of COVID‐19 patients. A survey invitation was emailed using the Japanese Society of Intensive Care Medicine's mailing list. Results: We analyzed 460 valid responses from among 976 responses. The N95/FFP2 mask (77%) was the most frequently used, although half of our respondents reported reuse of single‐use N95/FFP2 masks. The median duration (1 h) of uninterrupted PPE use per shift was less than that in the international study. The most common PPE‐related adverse event was experiencing intense heat (75%). Logistic regression analysis revealed that being a nurse was independently associated with experiencing intense heat. Conclusion: Shortage of PPE and frequent mask reuse were prevalent during the COVID‐19 pandemic in Japan. Intense heat is the most significant symptom, especially for nurses, even with short‐duration PPE use. Strategies to protect HCWs from dehydration and intense heatstroke are needed. Abstract : Comparison of shortages and reuse of single‐use personal protective equipment between Japan and an international survey during the COVID‐19 pandemic in 2020.